Analytical Study of Rectangular Concrete-Filled Tubes (RCFT) Connections using Finite Element Analysis under Cyclic Loading - Casita, Cintantya Budi; Suswanto, Budi; Komara, Indra (Trends in Sciences, 2022)
Recent condition of the earthquakes model has shown that rectangular concrete-filled tubes (RCFT) with weld connection are so brittle. According to the studies conducted, large damages are due to the cracking of the weld between the beam flange and the column face and inducing concentrated stresses in this area. One of the novel alternatives to reduce the stress concentration at the panel zone could be the use of the reduce beam section (RBS). Given the enormous impact of seismic behaviour and ductility of the panel zone, RBS moves plastic hinges formation at an appropriate distance from column face. In this study, 2 major model of RCFT with and without RBS have been modeled using ABAQUS computer program and compared under cyclic behaviour. The obtained result of this study showed that using RBS is more ductile and implied a good stability. It also will consider having better ductility than other connections. GRAPHICAL ABSTRACT